Synthesis and Structural Study of Some Mo(II) Carbonyl Complexes with Triazole and Oxadiazole Derivative - Obed, Sh. M. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A new carbonyl complexes of triazole and oxadiazole were synthesized. These complexes were identified and their structural geometric were suggested by using FT-IR and UV-Vis spectra, conductivity measurements and other chemical and physical properties. The spectra data (FT-IR, UV, Vis.) with the substantial aid of group theoretical calculations gave so many evidences for the proposed geometries and the type of bonding of these compounds